2021
DOI: 10.1093/jac/dkaa543
|View full text |Cite
|
Sign up to set email alerts
|

Effective antimicrobial combination in vivo treatment predicted with microcalorimetry screening

Abstract: Objectives The worldwide emergence of antibiotic resistance calls for effective exploitation of existing antibiotics. Antibiotic combinations with different modes of action can synergize for successful treatment. In the present study, we used microcalorimetry screening to identify synergistic combination treatments against clinical MDR isolates. The synergistic effects were validated in a murine infection model. Methods The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 17 publications
0
20
0
Order By: Relevance
“…Based on the definition, bactericidal activity was defined as a reduction of at least ≥3 log 10 of the total count of CFU/mL in the original inoculum. Therefore, the CLA plus OMD combination is shown to be bactericidal against Mab ( Kragh et al, 2021 ). Again, the CLA-BDQ combination also showed significant bacterial reduction, as similar with the checkerboard assay.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the definition, bactericidal activity was defined as a reduction of at least ≥3 log 10 of the total count of CFU/mL in the original inoculum. Therefore, the CLA plus OMD combination is shown to be bactericidal against Mab ( Kragh et al, 2021 ). Again, the CLA-BDQ combination also showed significant bacterial reduction, as similar with the checkerboard assay.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, combining ciprofloxacin, which attacks metabolically active layers, and colistin, which disrupts and kills the biofilm cells during low or inactive metabolic state, may render high therapeutic efficiency [50]. Several in vivo and in vitro studies have reported combinations that have been proved to be efficient in the treatment of biofilm-driven infections [50,51].…”
Section: Combined and Sequential Antimicrobial Therapiesmentioning
confidence: 99%
“…Molecular techniques are rapid and sensitive, but to date, they are not affordable for all laboratories [ 7 ]. There are also groups working on the use of several techniques, such as flow cytometry, droplet-based microfluidics, calorimetry, or spectroscopy, in order to obtain AST results in less than 2 h [ 8 , 9 , 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%